Introduction: Euroscepticism, from the margins to the mainstream. Issue 3 (June 2015) - Brack, Nathalie; Startin, Nicholas
With the advent of the Eurozone crisis, Euroscepticism has become increasingly mainstreamed. This is discernible across Europe at the level of public opinion, among political parties and civil society groups, within the EU institutions themselves and in terms of changing and more challenging media discourses. Against the backdrop of the 2014 European elections and a potential referendum on UK membership of the EU, the purpose of this article is to introduce an evolving debate. It begins with discussion of the 'state of the art' with regard to the study of Euroscepticism, before focusing on the significance of the latest European elections themselves. It then provides an overview of the various articles in the collection, explaining their relevance in helping to unravel the complexity and diversity of opposition towards 'Europe' and the extent to which Euroscepticism has become part of the mainstream with regard to European political debate.